2015
DOI: 10.1016/j.bbagrm.2014.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Functional interactions among members of the MAX and MLX transcriptional network during oncogenesis

Abstract: The transcription factor MYC and its related family members MYCN and MYCL have been implicated in the etiology of a wide spectrum of human cancers. Compared to other oncoproteins, such as RAS or SRC, MYC is unique because its protein coding region is rarely mutated. Instead, MYC’s oncogenic properties are unleashed by regulatory mutations leading to unconstrained high levels of expression. Under both normal and pathological conditions MYC regulates multiple aspects of cellular physiology including proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
142
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(161 citation statements)
references
References 271 publications
11
142
0
Order By: Relevance
“…Both MYC and MXD1 heterodimerize with MAX for DNA binding to target E-box motifs in gene promoters, and they mediate opposing effects on cells. MYC promotes cell proliferation and altered metabolism, while MXD1 promotes cell cycle arrest and differentiation (44). We found that KLF4 decreases MYC expression and decreases MYC downstream metabolic target genes in myeloid leukemia cells.…”
Section: Discussionmentioning
confidence: 70%
“…Both MYC and MXD1 heterodimerize with MAX for DNA binding to target E-box motifs in gene promoters, and they mediate opposing effects on cells. MYC promotes cell proliferation and altered metabolism, while MXD1 promotes cell cycle arrest and differentiation (44). We found that KLF4 decreases MYC expression and decreases MYC downstream metabolic target genes in myeloid leukemia cells.…”
Section: Discussionmentioning
confidence: 70%
“…Importantly, our recent review of the TCGA expression data indicated that multiple components of the network are simultaneously expressed in a wide range of both normal tissues and cancers, and that most tumor types show a specific expression pattern of MAX/MLX network members, arguing that each tissue has a distinct balance among members of the network. 9 In support of this hypothesis, Myc elicits alternative metabolic responses when overexpressed in murine lung or liver tissues, which predominantly express either MondoA or Chrebp. 10 Thus, evaluating the cell-or tissue-specific distribution and role of MAX/MLX network members, alone and in combination, will contribute to our understanding of both cancer cell metabolic flexibility and vulnerability.…”
mentioning
confidence: 73%
“…A unique property of the Max/Mlx network is its capacity to sense and respond both to mitogenic signals and nutrient availability (Diolaiti et al, 2014; O’Shea and Ayer, 2013). In this study we provide evidence that the MondoA-Mlx heterodimer is required for Myc-driven transcriptional reprogramming of cellular metabolism and tumor growth.…”
Section: Discussionmentioning
confidence: 99%